The Number of Frames on ECG-Gated 18F-FDG Small Animal PET Has a Significant Impact on LV Systolic and Diastolic Functional Parameters - Christoph Eissler; Rudolf A. Werner; Paula Arias-Loza; Naoko Nose; Xinyu Chen; Martin G. Pomper; Steven P. Rowe; Constantin Lapa; Andreas K. Buck; Takahiro Higuchi (Molecular Imaging, 2021)
Objectives. This study is aimed at investigating the impact of frame numbers in preclinical electrocardiogram- (ECG-) gated 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) on systolic and diastolic left ventricular (LV) parameters in rats. Methods. 18F-FDG PET imaging using a dedicated small animal PET system with list mode data acquisition and continuous ECG recording was performed in diabetic and control rats. The list-mode data was sorted and reconstructed with different numbers of frames (4, 8, 12, and 16) per cardiac cycle into tomographic images. Using an automatic ventricular edge detection software, left ventricular (LV) functional parameters, including ejection fraction (EF), end-diastolic (EDV), and end-systolic volume (ESV), were calculated. Diastolic variables (time to peak filling (TPF), first third mean filling rate (1/3 FR), and peak filling rate (PFR)) were also assessed. Results. Significant differences in multiple parameters were observed among the reconstructions with different frames per cardiac cycle. EDV significantly increased by numbers of frames (353.8 ± 57.7 μl∗, 380.8 ± 57.2 μl∗, 398.0 ± 63.1 μl∗, and 444.8 ± 75.3 μl at 4, 8, 12, and 16 frames, respectively; ∗P<0.0001 vs. 16 frames), while systolic (EF) and diastolic (TPF, 1/3 FR and PFR) parameters were not significantly different between 12 and 16 frames. In addition, significant differences between diabetic and control animals in 1/3 FR and PFR in 16 frames per cardiac cycle were observed (P<0.005), but not for 4, 8, and 12 frames. Conclusions. Using ECG-gated PET in rats, measurements of cardiac function are significantly affected by the frames per cardiac cycle. Therefore, if you are going to compare those functional parameters, a consistent number of frames should be used.